Enhancing Career Planning with Thinking Share Technique Classic Guidance Services - Nur Lathifah; Dini Rakhmawati; Chr Argo Widiharto (Department of Guidance and Counseling, FIP, Undiksha, 2019)
Career planning is a process for students to develop and implement an activity in order to achieve the desired career. These activities generally contains a variety of academic activities in accordance with a career. But, there are many students are confused how to plan his career. Based on the planning from the objective of this study is to determine the effectiveness of the classical counseling services using think pair share technique concerning on the career planning class in X MA Futuhiyyah 2 Mranggen. This research used quantitative methods using true experimental design Pretest-Posttest Control Group Design. In this study were taken from two sample classes using cluster random sampling technique. The results of the data pretest-posttest processing test results obtained hepotesis ie = 8.507 ≥ = 2,000 then from these results we can conclude that there is the enhancement of the classical service technique to think pair share on career planning the students’ in X class MA Futuhiyyah 2 Mranggen Demak